KONSEP KURIKULUM PENDIDIKAN ISLAM PERSPEKTIF MUHAMMAD ABDUH - Salsabila Yufi Arida; Riza Rosiana; Moh. Faizin, M.Pd.I (STAI Nurul Falah Airmolek, 2026)
This article discusses the concept of the Islamic education curriculum from the perspective of Muhammad Abduh, a prominent modern Islamic reformer from Egypt. The main focus is to analyze how Abduh’s ideas on education and curriculum reform can inspire the development of contemporary Islamic education systems. Using a descriptive qualitative approach, the study reveals that Abduh emphasized rationality, freedom of thought, and the integration of religious and secular sciences within the Islamic education curriculum. His concept remains relevant in addressing globalization challenges and the intellectual stagnation of the Muslim community.